The Sky as a Compass: The Traditional Navigation System of the Sea Nomads (Orang Laut) of Gara Island - Aubray Mariel Ariestho; Novita Mandasari Hutagaol; Tri Tarwiyani; Fitri Yanti; Arnesih Arnesih (Regalia Institute, 2026)
This study examines the traditional maritime knowledge system of the Orang Laut community on Gara Island, Batam City, Riau Islands Province. It aims to analyze local knowledge related to stars, the moon, ocean currents, seasons, winds, and natural signs used for navigation and maritime activities. The research employs the oral history method to reconstruct the development of this knowledge system from 1991 to 2026, with data collected through in-depth interviews and supported by relevant literature and documents. The data were analyzed using maritime anthropology and ethnoastronomy approaches. The findings indicate that the Orang Laut community possesses an ecological knowledge system developed through long-term interaction with the marine environment and transmitted across generations. This knowledge functions not only as a traditional navigation system but also as a foundation of cultural identity and ecological adaptation. The study further reveals that modernization and coastal development have contributed to the transformation of traditional maritime practices while simultaneously threatening the continuity of indigenous maritime knowledge. These findings highlight the importance of preserving local maritime knowledge as part of the cultural heritage of coastal communities.